Beliefs and attitude toward the Evidence-Based Practice of latin american speech audiologists exclusively dedicated to clinical and educational practice - Briones Rojas, César; León Godoy, Alexis; Osorio Viarengo, Natalia; Oyarzún Díaz, Patricia (Revista de Investigación en Logopedia, 2023)
Evidence-Based Clinical Practice (EBP) suggests to speech therapist incorporating actions aimed at responding to the needs of users in specific contexts. These actions include raising questions, reviewing, and analyzing critically the available evidence; decision-making, integrating clinical experience, evidence, and user preferences. Despite this paradigm has been positioned in the discipline in the last decade, its implementation results complex for professionals who are completely dedicated to clinical and / or educational practice, since the guidelines have come primarily from speech therapists who are not necessarily immersed in tasks directly related to the user’s service. The objective of the present study is to analyze the beliefs and attitude towards EBP of dedicated speech therapists to clinical and / or educational full-time workers in different Latin American countries. A qualitative study, based on grounded theory is carried out. It was conducted by performing semi-structured interviews with speech therapists living in Argentina, Paraguay, Chile, Peru, Colombia, Uruguay, and Costa Rica. A total of 9 professionals answered the interview. Most of the respondents considers that EBP is limited to scientific publications and difficult their implementation in their work context, mainly due to the lack of time associated with reviewing updated scientific literature. As a conclusion it can be stated that there is an erroneous belief in conceptual terms about the real meaning of EBP, which generates ambiguous attitudes towards the mentioned paradigm. To Latin American level it is necessary to consider about the formation of speech therapists allowing them from undergraduate to handle a greater number of resources for decision-making in both evaluation, and intervention to reduce the gap between researchers and those who are eminently dedicated to clinical practice with a view to the actual implementation of EBP.